Video documental sobre el muralismo con contenido político del artista Pavel Égüez. - Pérez Bravo, Hernán Leonardo (2016)
This is a documentary which main subject is the politically content in the murals by artist Pavel Égüez, a view from the painter`s perspective who tells us his experience as a muralist, the thematic line of his work, education, history of mural and the influence of Oswaldo Guayasamín. The documentary lasts 30 minutes and 45 seconds and is entitled: Mural. The art close to everyone and talks about muralism as an expression of art in the public space, the subject of his political and social status, and the tradition of Latin American art within what is known as social art The first phase of this audiovisual work addresses issues on how a mural is made regarding the sponsorship and recruitment of the artist by a public or private institutions. Likewise, the history of mural painting as an expression of public art is addressed, from the conception of the city and urban areas. Using resources such as interviews and photographs, this work reflects the views of characters such as art critics, graffiti artists like Apitatan who from its artistry as a urban artist tells about how it is to create a mural. Also the sociologist Natalia Sierra provides a direct criticism of the work of Pavel Égüez from a philosophical and sociological point of view.